The Impact of Work Family School Conflict on Work Stress in Doctoral Management Students at Mercu Buana University - Muchtadin, Muchtadin; Nurul Sukma Lestari (MID Publisher International, 2024)
This research is intended to see the effect of work family school conflict on work stress. The study population was 61 doctoral management students in active status who were members of the whatsapp group